Determining the Function of Social Referencing: The Role of Familiarity and Situational Threat - Ehli, Samantha; Wolf, Julia; Newen, Albert; Schneider, Silvia; Voigt, Babett (Frontiers in Psychology, 2020)
In ambiguous situations infants have the tendency to gather information from a social interaction partner to regulate their behavior (SR, social referencing). There are two main competing theories concerning SR’s function. According to social-cognitive information seeking accounts, infants look at social interaction partners to gain information about the ambiguous situation. According to co-regulation accounts, infants look at social interaction partners to receive emotional support. This review provides an overview of central developments in SR-literature in the last 24 years since the seminal review by Baldwin & Moses (1996). We focus on the role of situational aspects such as familiarity of SR-partners and situational threat, not only for SR (looking), but also for subsequent behavioral regulation (exploration, affect). As the competing accounts make different predictions concerning both contextual factors, this may reveal novel insights into the function of SR. Findings showed that a higher familiarity of SR-partners consistently results in decreased looking (cf. social-cognitive accounts) and that higher threat remains largely understudied, but seems to increase looking in the first few studies (cf. co-regulation accounts). Concerning the behavioral regulation (exploration, affect) findings are mixed. We point out that moving towards a more complex situatedness may help to disentangle the heterogeneous results by considering the interaction between familiarity and threat rather than investigating them in isolation. From a general perspective, this review underlines the importance of situational factors and their interaction in eliciting a phenomenon, such as SR, but also in determining the nature of the phenomenon itself.